Effect of wearing different types of face masks during dynamic and isometric resistance training on intraocular pressure - Vera, J.; Redondo, B.; Koulieris, G. A.; Jiménez, R.; García-Ramos, A. (Clinical and Experimental Optometry, 2023)
Clinical relevance: The use of face masks has demonstrated to be an effective strategy to prevent transmission of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Wearing face masks, mainly Filtering Face Piece 2 (FFP2) masks, during exercise practice has demonstrated to affect several physiological measures. Background: This study was aimed at assessing the intraocular pressure (IOP) behaviour during the execution of the dynamic and isometric biceps-curl exercise with a surgical and FFP2 face mask. Methods: Twenty two physically active young adults performed sets of 10 repetitions against the 10-RM (repetition maximum) load and 1-minute isometric effort against a load 15% lower than the 10-RM load with the FFP2 and surgical mask and without any mask. A total of six exercise sets (3 experimental conditions [FFP2, surgical and control] × 2 exercise modalities) were performed. A rebound tonometer was used to measure IOP before, during (10 measurements), and after (30-seconds of passive recovery) each training set. Results: At rest, there were not statistically significant IOP differences (p = 0.222). During dynamic exercise, there was a progressive IOP rise (p < 0.001), and a higher IOP response with the FFP2 than without the mask (corrected p-value = 0.003). For the isometric exercise, there was a greater IOP response as a function of accumulated effort (p < 0.001), which was dependent of the face mask used (FFP2> surgical>control; corrected p-values< 0.01). Conclusions: The FFP2 masks cause a heightened IOP response during the execution of dynamic and isometric biceps-curl exercise, suggesting that, when possible, glaucoma patients should limit the use of FFP2 masks during resistance training.